HUMAN CAPITAL AS A FACTOR OF SUSTAINABLE DEVELOPMENT IN UZBEKISTAN - Sattikulova G. A (Antis Publisher, 2025)
Objective: This article analyzes the significance of human capital as a key resource for sustainable socio-economic development, drawing on international experience and current trends in Uzbekistan. Method: Special attention is paid to the components of the Human Development Index (HDI), including life expectancy, the level of education, and gross national income (GNI) per capita. Results: The dynamics of Uzbekistan’s HDI indicators for 2015–2023 are examined in detail. Novelty: Drawing on international experience and current trends in Uzbekistan.